The distribution and population density of bornean tarsier, tarsius bancanus borneanus (Elliot) in secondary and rehabilitated forests of Universiti Putra Malaysia, Bintulu Sarawak Campus, Sarawak, Malaysia - Muhd Sahimi, Hani Nabilia; Chubo, John Keen; Mohd. Top @ Mohd. Tah, Marina; Saripuddin, Noor Bahiah; Ab Rahim, Siti Sarah (Penerbit Universiti Sains Malaysia, 2018)
Tarsius bancanus borneanus was first reported by Elliot in 1990 which an endemic species that can be found on the Island of Borneo consisting of Sabah and Sarawak of Malaysia, Brunei Darussalam and Kalimantan, Indonesia. This sub-species has been listed as a totally protected animal under the Sarawak Wild Life Protection Ordinance (1998) and vulnerable by the International Union for Conservation of Nature (IUCN). The present study was conducted at Universiti Putra Malaysia Bintulu Campus (UPMKB), Sarawak from October 2014 till March 2015. Through mark and recapture sampling covering an area of 37 ha of secondary forest patches and 7.13 ha of rehabilitated forest, a total of 16 tarsiers were captured using mist nets while one tarsier was recapture. The population density was 38 individuals/km2 was captured using mist nets in the secondary forest while 28 individuals/km2 was recorded for the rehabilitated forest. Using the catch per unit effort (net hour) method, the average time for capturing tarsiers in the secondary forest patches was 26.6 net hour per animal and 30.0 net hour per animal in the rehabilitated forest. The presented results provides information on the presence of tarsiers in both the secondary and rehabilitated forests of UPMKB, Sarawak, Malaysia which underlines the conservation value of these forested areas.